Determining toxic metal concentration changes in landscaping plants based on some factors - Sevik, Hakan; Cetin, Mehmet; Ozel, Halil Baris; Pinar, Bekir (Springer Science and Business Media LLC, 2019)
Toxic metals are one of the most culpable air pollutants. They do not dissolve naturally. Rather, they tend to be bioaccumulative, and some of them have toxic or carcinogenic effects even at low measures. Therefore, the ability to measure and monitor toxic metal concentrations in the air is vital in fighting pollution. To achieve this, bioindicators are widely used due to their efficiency and global availability. Bioindicators are plants that accumulate some of the toxic metals found in the soil or air. This study aims to determine the differences in toxic metal concentrations depending on plant species, plant organelles, and traffic density in certain landscaping plants grown in Kastamonu town center. The results showed that the elements subjected to the study varied significantly between the different species. The highest accumulation values of such metals were obtained in cherry plum (Prunus cerasifera), and the lowest values of all metals were found in the European ash (Fraxinus excelsior). Based on our observations in this study, we determined that the most suitable species used as biomonitor is the cherry plum (Prunus cerasifera). We noticed that the concentrations of the metals differed significantly according to the species. The biggest difference recorded was five times more in Ni metal concentration. The concentrations of the studied elements were also varied depending on organelles and on traffic density, which will be discussed in detail in this paper.
Keywords: Ni; Health, Toxicology and Mutagenesis; Elements; Air Quality; Cd; Landscape Plant; Biomonitor; Air Pollution; Toxic Metals; Organelle; Traffic; Zn; 13. Climate action; 11. Sustainability